#TITLE_ALTERNATIVE# - RAQUEL NATALIA TOREH ( NIM : 10208091); Pembimbing Tugas Akhir : Dr. Eng. Suprijadi, KIRSTIE
Human in their activity is definitely must make a direct contact with the surface of something. This final project discussed the detail of surface growth. Talk about surface, the surfaces on earth are almost rough and usually formed by deposition process. The formation process of those rough surfaces can be described by three simple models, namely Random deposition (RD), Ballistic deposition (BD), and Random deposition with surface relaxation (RDSR), which follow its own same rules, universality class. Each model follow scaling relation (exponents) which can be described by experiment, discrete model, and continuum equation. All of the three models can be described using the equations, Edwards-Wilkinson (EW) equation, and the Kardar-Parisi-Zhang (KPZ) equation. RDSR are described by EW equation and BD are described by KPZ. From the models that we made, we got scaling exponents. For RD model we got β=0.5005; for BD model β=0.2873, α=0.4651, z=1.5132; and for RDSR model α=0.46; β=0.2547; z=1.806. The three models can also be used to learn how to make a thin film (semiconductor material), a real case and sufficiently developed lately one. If we add some physical parameters to the models, then it can be used to explain the Molecular Beam Epitaxy (MBE). In MBE, as the temperature increase, the surface will be smoother on the other hand as the temperature decrease, the surface will be rougher. The value of β that we got is smaller as the temperature increase for every different length of system. For MBE βefektif≈0,375.